COMPARATIVE ANALYSIS OF LEADERSHIP STYLES: IMPLICATIONS FOR ORGANIZATIONAL PERFORMANCE AND EMPLOYEE SATISFACTION - Ghummid Husam Aboalasad Emhemad; Germaine Solie; Ahmed Abdullah Olais; Ooi Kok Loang (International Journal of Accounting, Finance and Business, 2023)
This paper offers a thorough analysis of 20 studies on employee satisfaction, organisational performance, and leadership styles. The results of these studies demonstrate how important leadership styles are in determining organisational results and employee experiences. While democratic, transformational, and transactional leadership styles had positive effects on both organisational performance and employee satisfaction, autocratic leadership styles were consistently linked to lower levels of employee satisfaction. The most effective style of leadership emerged, with higher levels of organisational commitment and employee satisfaction being consistently predicted by it. Theoretical ramifications of these findings validate democratic and transformational leadership styles' efficacy in achieving organisational objectives and raising employee satisfaction, which advances leadership theory. The practical ramifications indicate that businesses should give top priority to adopting leadership philosophies that give workers agency, involve them in decision-making, and foster a sense of belonging. The creation of inclusive and participatory work environments that promote candid communication, teamwork, and shared decision-making is advised for managers. Managers can inspire and motivate staff members, promote innovation, and offer tailored support by exhibiting transformational leadership traits.